Laparoscopic Sleeve Gastrectomy Outcomes in Patients with Polycystic Ovary Syndrome. Issue 3 (March 2019) - Yheulon, Christopher G.; Millard, Anthony J.; Balla, Fadi M.; Jonsson, Arinbjorn; Constantin, Tinav; Singh, Arvinpal; Srinivasan, Jahnavi; Stetler, Jamil; Patel, Ankit; Lin, Edward; Davis, S. Scott
Polycystic ovary syndrome (PCOS) is a common disease among the bariatric population. However, there are limited data regarding the impact of laparoscopic sleeve gastrectomy (SG) on these patients. The study was conducted at University Hospital, United States. The purpose of this study was to examine per cent excess body weight loss (%EWL) and diabetes control in patients who have PCOS compared with those without PCOS. A total of 550 female patients underwent SG between December 2011 and October 2016. Retrospective analysis was completed to include follow-up data at 1, 3, 6, and 12 months and yearly after that. Outcomes measured were %EWL and hemoglobin A1c (HgbA1c). The mean and median follow-up for the entire cohort was 21 and 15 months, respectively. Seventy-eight per cent of patients completed at least 12 months of follow-up for %EWL, although only 21 per cent had similar follow-up for HgbA1c. PCOS patients had similar age (36.3 vs 36.2 years, P = 0.90), preoperative BMI (47.2 vs 47.2, P = 0.99), preoperative HgbA1c (6% vs 5.8%, P = 0.31), conversion rate to gastric bypass, and other associated comorbidities compared with non-PCOS comparisons. There was no difference in %EWL at 12-month (49.7% vs 53.1%, P = 0.53) or 24-month (43% vs 49.8%, P = 0.46) postoperative intervals. There was no difference in absolute change of HgbA1c at 12 months (-0.47% vs -0.67%, P = 0.39). SG has equivalent short-term results in %EWL and reduction in HgbA1c for patients who have PCOS and those who do not.